MORTALITY RATE OF SITOPHILUS ZEAMAIS IN LOW TEMPERATURE STORAGE - David Septian Sumanto Marpaung (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Maize is one of important comodities contributed as food consumption and other bioproducts to the world. As high demand of maize in global must be followed its avalaibility in markets. Decline the post-harvest losses along maize distribution will not only keep the avalaibility in markets, but also solve the food security. One of post-harvest losses causes is pest, especially in maize storage. The temperature treatment to control S.zeamais, a major insect found in maize storage, becomes potential action in order to reduces the post-harvest losses. The aim of this study was to investigate the S.zeamais mortality rate and physical changes of maize kernel under low temperature condition. The S.zeamais was cultured within 4 months before used for experiments. The 2 different low temperature conditions and 1 control treatment were used in this study. The results showed that the temperature of maize kernel was changed, indicated the movement of maize from room temperature to low temperature storage is occurred. Furthermore, the low temperature treatments, the maize moisture content was slightly changed compared to the control treatment. In addition, there is no chilling injury issue to maize kernel. However, the unknown mechanism of S.zeamais protection to the low temperature was found in the Low Temperature I treatment through the finding of hole grain. In the mortality rate, the highest mortality rate was found at Low Temperature II treatment (95.30 ±11.54%). These findings suggests that low temperature treatment could be the action for maize pest management, especially in the storage.